Methodical approaches of land registration formation of recreational land use of water protection zones and coastal protective strips - Yusypenko, O. (Land Management, Cadastre and Land Monitoring, 2021)
Today, in the conditions of transformational transformations, the recreational potential of reservoirs is used only partially, in connection with the priority of development of other branches of activity (health-improving). This is despite the fact that the value of water resources is involved in the processes of all areas of activity. That is why the issue of land management formation of recreational land use of water protection zones and coastal protection strips requires an integrated approach. Which is carried out through the assessment of recreational and tourist potential of territories and settlements to emphasize the characteristics and features that are important in the implementation of recreational activities and have a direct impact on the planning organization of land use.For the purpose of verifying the set of general intelligence, the author schematically presents the concept of "structural components that form the land use of cultural landscapes ". It has been established that in a city, the assessment of the attractiveness of land use of landscapes for recreational activities should determine the originality of recreational land use in accordance with regional and local specifics and landscape diversity. It has been seen that as a result of using various methodological approaches to assessing the recreational potential of land use of the water protection zone and the coastal protection strips, the following should be established: the recreational capacity of land use of the territory; permissible recreational load; recreational digression. In addition, according to the results of the assessment, it is proposed to divide the recreational land use of the territories of water protection zones and coastal protection strips by popularity rating, in particular, with high, medium and low potential values. As an example, the state of recreational potential in Kyiv was considered and it was established that the land management arrangement of the city needs an immediate solution for further development of recreational land use. Also, the author, due to the lack of established boundaries of water protection zones, presents a characteristic of acute social and environmental problems of land use of water bodies in Kyiv.It has been established that if there are restrictions on the use of land and other natural resources, but there is no information about them, then there is a possibility of the occurrence of various types of damage to the land use of water protection zones and coastal strips. That is why, it is proposed to allocate functional land use zones of the coastal protection strips by types of development, which will allow more efficient use of the existing potential of recreational land use of water protection zones and coastal protection strips within Kyiv and its greening and generally increase capitalization.Keywords: recreational land use, water protection zones, coastal protection strips, functional areas